Pengembangan Lembar Kerja Siswa Berdasarkan Pratinjau Pertanyaan Baca Refleksi Ucapkan Tinjauan (PQ4R) dalam Pembelajaran Membaca Pemahaman Bahasa Indonesia Kelas IV Sekolah Dasar - Sariska, Apriana (Jurnal Pembelajaran dan Pengajaran Pendidikan Dasar, 2025)
This study aims to determine the need for PQ4R-based LKPD in reading comprehension of Indonesian in grade IV in elementary school, to find out the development of LKPD products using the PQ4R method for reading comprehension in grade IV SD. This research is research and development (R&D). The object of research is the development of PQ4R-based LKPD in learning to read and understand Indonesian language lessons in fourth grade elementary school. The results showed that the LKPD was oriented to the PQ4R method on reading comprehension in grade IV SD as a development product that was feasible to use. From the research, it can be concluded that what teachers and students need are (1) PQ4R-based LKPD for reading comprehension of Indonesian class IV lessons at SDN 18 Kaur, (2) LKPD is designed with attractive color and image display, (3) PQ4R-based LKPD is in accordance with level of student characteristics and easy to understand. The development of LKPD products using the PQ4R method on reading comprehension in class IV SDN 18 Kaur was carried out by analyzing the needs of teachers and students, then validation was carried out by the validation team after improvements based on suggestions from the validator, limited trials were carried out to students, asked for student responses and teacher. The PQ4R-oriented worksheets on reading comprehension in grade IV SDN 18 Kaur have been declared eligible by the validation team after the validator validates the PQ4R-based worksheets. The response of teachers and students to the PQ4R method-oriented LKPD on reading comprehension in grade IV SDN 18 Kaur is positive, this is evident from the questionnaire given to teachers and students.